Effectiveness of a multidisciplinary critical pathway based on a computerised physician order entry system for ST-segment elevation myocardial infarction management in the emergency department: a retrospective observational study - Park, Yoo Seok (BMJ Open, 2016)
OBJECTIVES: The purpose of this study was to investigate whether a multidisciplinary organised critical pathway (CP) for ST-segment elevation myocardial infarction (STEMI) management can significantly attenuate differences in the duration from emergency department (ED) arrival to evaluation and treatment, regardless of the arrival time, by eliminating off-hour and weekend effects. DESIGN: Retrospective observational cohort study. SETTING: 2 tertiary academic hospitals. PARTICIPANTS: Consecutive patients in the Fast Interrogation Rule for STEMI (FIRST) program. INTERVENTIONS: A study was conducted on patients in the FIRST program, which uses a computerised physician order entry (CPOE) system. The patient demographics, time intervals and clinical outcomes were analysed based on the arrival time at the ED: group 1, normal working hours on weekdays; group 2, off-hours on weekdays; group 3, normal working hours on weekends; and group 4, off-hours on weekends. PRIMARY AND SECONDARY OUTCOME MEASURES: Clinical outcomes categorised according to 30-day mortality, in-hospital mortality and the length of stay. RESULTS: The duration from door-to-data or FIRST activation did not differ significantly among the 4 groups. The median duration between arrival and balloon placement during percutaneous coronary intervention did not significantly exceed 90 min, and the proportions (89.6–95.1%) of patients with door-to-balloon times within 90 min did not significantly differ among the 4 groups, regardless of the ED arrival time (p=0.147). Moreover, no differences in the 30-day (p=0.8173) and in-hospital mortality (p=0.9107) were observed in patients with STEMI. CONCLUSIONS: A multidisciplinary CP for STEMI based on a CPOE system can effectively decrease disparities in the door-to-data duration and proportions of patients with door-to-balloon times within 90 min, regardless of the ED arrival time. The application of a multidisciplinary CP may also help attenuate off-hour and weekend effects in STEMI clinical outcomes.